An Inquiry into Teachers' and Parents' Experiences of Radio-Based Instruction and Modular Distance Learning in Early Childhood Education - Joyce V. Raguini (Journal of Elementary and Secondary School, 2024)
This study examines the perspectives and experiences of educators and caregivers regarding radio-based instruction (RBI) and modular distance learning (MDL) in early childhood education. Semi-structured interviews with 10 parents and 6 kindergarten teachers in the Bay Sub-Office, Laguna, Philippines revealed significant challenges in access to technology, parental involvement, and socio-emotional development of learners. The findings underscore the need for clear instructional guidance and accessible resources. The study concludes that guardians’ participation, engagement, instructional clarity, and material accessibility are crucial for effective remote learning. As a result, the RADIO model and a comprehensive course outline were developed to address these needs, emphasizing resilience, collaboration, and inclusivity. Recommendations include enhancing technological infrastructure to ensure equitable access, implementing customized parental education programs, integrating socio-emotional learning (SEL) into the curriculum, providing targeted professional development for educators, and establishing continuous research and evaluation mechanisms to adapt strategies effectively. These recommendations foster an inclusive and dynamic educational ecosystem, enhance early childhood education and ensure quality remote learning experiences.